NEGOTIATING THE INTERNATIONAL AGREEMENT ON AGRICULTURE AFTER DOHA ROUND - INDIAN PERSPECTIVE (NATIONAL CAPITAL LAW JOURNAL, 2008)
NA
Keywords: International regulations under GAIT 1947; Agreement on Agriculture (AoA); World Trade Organization (WTO); Domestic support; Export subsidies; Aggregate Measurement of Support (AMS); Food security; Rural livelihood; Protectionism; Negotiations; Negotiation Law; Gross Domestic Product; Law